Knowledge Management as an Enabler of Effective Career Services in Institutions of Higher Learning: The Case of the Singapore Management University - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2005)
The implementation of knowledge management frameworks in institutions of higher learning has become an imperative in an age of globalisation, accelerated technological change and increased competition. The paper describes and analyses a crucial element of a KM-enabled tertiary educational institution, namely SMU's OnTRAC system. Developed and managed by SMU's Office of Career Services, the SMU OnTRAC System is a user-friendly and highly interactive online system designed to facilitate students, employers, administrators and organisations to information on Training, Recruitment, Attachment and Community Service. The purpose is to give employers, organisations, administrators and students expeditious online World Wide Web and password secured access to a repository of information on talents, facilitated by an advanced, state-of-the-art search engine to provide an effective platform to match seekers to the right talents and opportunities. It is argued that such systems need to be integrated into a holistic KM strategy so as to ensure effective organisational performance.